Plan de comercialización: estrategia de vinculación entre los pequeños productores agropecuarios del cantón de San Carlos y hoteles y restaurantes de Fortuna - Alvarado-Herrera, María Ilda (Instituto Tecnológico de Costa Rica, 2018)
Local governments are ideal institutions to the promotion of local development strategies and policies, which allow better economic conditions and generate opportunities for its inhabitants. The municipalities have the capacity to join efforts with other public and private institutions, to promote projects that contribute to the progress of the communities. The Municipality of San Carlos is aware of this condition, whence the present work seeks to determine what elements should be considered to an optimal strategy for linking the agricultural sector of San Carlos with the Fortuna hotels and restaurants. The research has a quantitative approach, the design includes a descriptive scope with some variables which are analyzed in their natural environment, this research is non-experimental and transversal. The interviews and the structured survey are the methods used to collect the information. Three study populations were established, the micro, small and medium agricultural producers of San Carlos, Fortuna hotels and restaurants. At the end of the investigation, an important interest was identified among the studied populations to achieve the productive linkage within San Carlos, the producers have several weaknesses that must be addressed with the cooperation of institutions that allow exploiting the strengths of the sector, with the purpose of taking advantage of the opportunities presented by the hotel and restaurant market.
Proyecto de Graduación (Bachillerato en Administración de Empresas). Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas. 2018
Keywords: Comercio; Producción agropecuaria; Producción agrícola; Presupuesto; Turismo; Marketing; Research Subject Categories::SOCIAL SCIENCES::Business and economics; Clientes